Efektivitas Penerapan Sistem Informasi Akuntansi, Kecanggihan Teknologi, Internal Locus Of Control dan Kinerja Pegawai - Devi, Ni Made Kusuma; Dharmadiaksa, Ida Bagus (E-Jurnal Akuntansi; Vol 31 No 6 (2021)DO - 10.24843/EJA.2021.v31.i06.p07, 2021)
This study aims to analyze and empirically test the effect of the effectiveness of the application of accounting information systems, information technology and internal locus of control on the performance of the Bali Provincial Inspectorate employees. This study uses non-probability sampling, namely purposive sampling method with the criteria of employees who use accounting information systems and use computers in carrying out their work activities. Questionnaires were distributed directly to employees with the analytical technique used was multiple linear regression. Based on the analysis results show that the effectiveness of the application of accounting information systems, information technology and internal locus of control has a positive and significant effect on employee performance. Keywords: Effectiveness Of The Application Of Accounting Information Systems; Information Technolog;, Internal Locus Of Control; Employee Performance.